2019
DOI: 10.1177/0267659119858853
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection is associated with subarachnoid hemorrhage and infectious intracranial aneurysm in left ventricular assist device

Abstract: Bloodstream infection is the leading cause of mortality in left ventricular assist device. Bloodstream infection is a risk factor for intracranial hemorrhage. We report three left ventricular assist device recipients who presented with bloodstream infection and developed subarachnoid hemorrhage. Case 1, a 37-year-old male with non-ischemic cardiomyopathy with HeartMate II, presented with confusion and found to have serratia bloodstream infection and left frontal lobe subarachnoid hemorrhage. Cerebral angiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The postoperative infections in patients with neurosurgical craniocerebral surgery are mostly happens in the body cavity or intracranial parts [ 14 ]. It’s been reported that postoperative infection in patients with cerebrovascular diseases, craniocerebral trauma and craniocerebral tumors is relatively high, and its possible causes are closely related to the types of surgery, surgical methods and the characteristics of surgery in patients with this disease [ 15 , 16 ]. Patients with cerebrovascular diseases and craniocerebral injuries mainly undergo emergency surgery in clinical settings, and there are often insufficient pre-operative preparations and incomplete debridement during surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative infections in patients with neurosurgical craniocerebral surgery are mostly happens in the body cavity or intracranial parts [ 14 ]. It’s been reported that postoperative infection in patients with cerebrovascular diseases, craniocerebral trauma and craniocerebral tumors is relatively high, and its possible causes are closely related to the types of surgery, surgical methods and the characteristics of surgery in patients with this disease [ 15 , 16 ]. Patients with cerebrovascular diseases and craniocerebral injuries mainly undergo emergency surgery in clinical settings, and there are often insufficient pre-operative preparations and incomplete debridement during surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee and colleagues reported an LVAD patient who developed a second CMA, following rupture of their initial CMA, which was successfully detected with CTA and treated with endovascular coiling. 5 As evidenced by the different types of organisms that have been described in our case report and others, the virulence of the organism itself appears irrelevant, and the mere presence of bacteremia in an LVAD patient should be a consideration for neurological imaging. In conclusion, clinicians should have a low threshold for neurological screening in bacteremic LVAD patients, regardless of the source of sepsis and infectious organism, as preventive interventions of CMAs can reduce the likelihood of rupture and fatal cerebral hemorrhage in this at-risk population.…”
Section: Discussionmentioning
confidence: 62%
“…IIA is rare, only comprising 0.7%-5.4% of all intracranial aneurysms and usually associated with infective endocarditis [4]. It is interesting that S. epidermidis being less virulent still causes mycotic aneurysm formation in LVAD patients [5][6][7][8][9][10][11]. In this case, the patient did not present with signs or symptoms of systemic inflammatory response syndrome (SIRS).…”
Section: Discussionmentioning
confidence: 99%